Development of a potent and selective chemical probe for the pleiotropic kinase CK2. Issue 4 (15th April 2021) - Wells, Carrow I.; Drewry, David H.; Pickett, Julie E.; Tjaden, Amelie; Krämer, Andreas; Müller, Susanne; Gyenis, Laszlo; Menyhart, Daniel; Litchfield, David W.; Knapp, Stefan; Axtman, Alison D.
Summary: Building on the pyrazolopyrimidine CK2 (casein kinase 2) inhibitor scaffold, we designed a small targeted library. Through comprehensive evaluation of inhibitor selectivity, we identified inhibitor 24 (SGC-CK2-1) as a highly potent and cell-active CK2 chemical probe with exclusive selectivity for both human CK2 isoforms. Remarkably, despite years of research pointing to CK2 as a key driver in cancer, our chemical probe did not elicit a broad antiproliferative phenotype in >90% of >140 cell lines when tested in dose-response. While many publications have reported CK2 functions, CK2 biology is complex and an available high-quality chemical tool such as SGC-CK2-1 will be indispensable in deciphering the relationships between CK2 function and phenotypes. Graphical abstract: Highlights: We developed a potent, selective, and cell-active chemical probe for CK2 We identified a negative control compound to be used with the CK2 probe Our selective chemical probe (SGC-CK2-1) is not broadly antiproliferative SGC-CK2-1 is the best available chemical tool to define the roles of CK2 in cells Abstract : Many papers have detailed the function(s) of casein kinase 2 (CK2). Characterization of CK2, however, has been confounded by the use of suboptimal inhibitors. Wells et al. have identified the best available chemical tool to use in illuminating the essential roles of this pleiotropic kinase.